"I Kind of Have a Goal When I Do It": The Phenomenology of Cultural Variability in Southeast Asian American Tricultural Emerging Adults. Issue 5 (October 2020) - Nguyen, Jacqueline; Ferguson, Gail M.
Cultural variability (CV) is a dynamic identity process by which individuals play up and play down their cultural identities from day to day. This study examines the phenomenology of CV in a unique group of tricultural Southeast Asian American (SEAA) emerging adults who identify with Asian American, White American, and hip hop cultures to understand how it is experienced, the reasons for its use, the extent to which it is conscious/agentic, and how three cultural identities are managed simultaneously. Interpretive phenomenological analyses reveal that CV was used consciously and involved making behavioral and cognitive changes to fit in with out-group members, educate others about SEAA culture, and to distance themselves from in-group members. Importantly, the centrality of SEAA identity most often remained stable despite playing up/down identities. Overall, findings suggest that CV is an essential identity negotiation strategy for tricultural emerging adults that is complementary to alternation/code-switching.